The Advaita worldview : God, world, and humanity - Rambachan, Anantanand, 1951- (SUNY series in religious studies., 2006)
"In this book, Anantanand Rambachan offers a fresh and detailed perspective on Advaita Vedanta, Hinduism's most influential and revered religious tradition. Rambachan, who is both a scholar and an Advaitin, attends closely to the Upanisads and authentic commentaries of Sankara to challenge the tradition and to reconsider central aspects of its current teachings. His reconstruction and reinterpretation of Advaita focuses in particular on the nature of brahman, the status of the world in relation to brahman, and the meaning and relevance of liberation." "Rambachan queries contemporary representations of an impersonal brahman and the need for popular, hierarchical distinctions such as those between a higher (para) and lower (apara) brahman. Such distinctions, Rambachan argues, are inconsistent with the non-dual nature of brahman and are unnecessary when brahman's relationship with the world is correctly understood. Questioning Advaita's traditional emphasis on renunciation and world-denial, Rambachan expands the understanding of suffering (duhkha) and liberation (moksa) and addresses socioeconomic as well as gender and caste inequalities. Positing that the world is a celebrative expression of God's fullness, this book advances Advaita as a universal and uninhibited path to a liberated life committed to compassion, equality, and justice."--Jacket.